2021
DOI: 10.1021/acs.inorgchem.0c03664
|View full text |Cite
|
Sign up to set email alerts
|

Recovering the Thermally Activated Delayed Fluorescence in Aggregation-Induced Emitters of Carborane

Abstract: The aggregation-induced emission (AIE) behaviors of carborane-based hybrid emitters have been extensively reported, while their combinations with the thermally activated delayed fluorescence (TADF) are still scarce. We designed and synthesized three Janus carboranes (the chemical structures resemble the double-faced god, Janus) Cb-1/2/3 with different carbazole moieties. All of the Janus carboranes exhibited quenched emission in solution with ΦPL (quantum efficiency of photoluminescence (PL)) lower than 0.01. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…As previously reported in the donor–acceptor configured carboranes, the short τ could be attributed to the extensive π⋯π interactions, which induced the triplet excited state annihilation. 42 Because these carboranes possessed the same TPA-Cb-Cz structure, it was conceivable that they all preserved the evident π⋯π interactions and this was most obvious in CB-Cz . Because of this drawback, they could behave as efficient photoluminescent materials in a white-light source by combining them with blue-LEDs (LED = light-emitting diodes) or by using molecular engineering, such as introducing branched substituents to diminish the π⋯π interactions, they could behave as electroluminescent materials because of the recovery of their potential TADF properties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously reported in the donor–acceptor configured carboranes, the short τ could be attributed to the extensive π⋯π interactions, which induced the triplet excited state annihilation. 42 Because these carboranes possessed the same TPA-Cb-Cz structure, it was conceivable that they all preserved the evident π⋯π interactions and this was most obvious in CB-Cz . Because of this drawback, they could behave as efficient photoluminescent materials in a white-light source by combining them with blue-LEDs (LED = light-emitting diodes) or by using molecular engineering, such as introducing branched substituents to diminish the π⋯π interactions, they could behave as electroluminescent materials because of the recovery of their potential TADF properties.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this drawback, they could behave as efficient photoluminescent materials in a white-light source by combining them with blue-LEDs (LED = light-emitting diodes) or by using molecular engineering, such as introducing branched substituents to diminish the π⋯π interactions, they could behave as electroluminescent materials because of the recovery of their potential TADF properties. 42…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, many types of the aryl-modified o-carborane dyads exhibit the aggregation-induced emission (AIE) property. [27,[44][45][46][47][48][49][50] Correspondingly, intense emission was observed around 400 nm in solution thio-CBH, meanwhile significant emission band around 650 nm was obtained in aggregation and crystal. From the solvatochromic behavior (Figures S2 and S3 and Table S2) and longer lifetimes, it was suggested that the emission band in the longer wavelength region should be obtained from the ICT state.…”
Section: Resultsmentioning
confidence: 99%